2011
DOI: 10.1074/jbc.m111.219071
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Transmembrane Binding Sites for p-Trifluoromethyldiazirinyl-etomidate, a Photoreactive Torpedo Nicotinic Acetylcholine Receptor Allosteric Inhibitor

Abstract: The excitatory nicotinic acetylcholine receptors (nAChRs) 2 and serotonin 5-HT 3 receptors and the inhibitory ␥-aminobutyric acid type A receptors (GABA A Rs) and glycine receptors are members of the Cys-loop superfamily of neurotransmittergated ion channels (1-3). Models of the three-dimensional structures of these receptors can be derived from the cryoelectron microscopy structure of the Torpedo nAChR in the absence of agonist (4) and from the high resolution crystal structures of distantly related prokaryot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
69
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(71 citation statements)
references
References 42 publications
1
69
1
Order By: Relevance
“…Our results establish that dFBr can photoincorporate into a wide range of amino acid side chains; however, we did not find photolabeling of amino acids in the TMD that contribute to the known intersubunit or intrasubunit binding sites for Torpedo nAChR positive and negative allosteric modulators (Nirthanan et al, 2008;Hamouda et al, 2011Hamouda et al, , 2014Jayakar Fig. 10.…”
mentioning
confidence: 46%
See 2 more Smart Citations
“…Our results establish that dFBr can photoincorporate into a wide range of amino acid side chains; however, we did not find photolabeling of amino acids in the TMD that contribute to the known intersubunit or intrasubunit binding sites for Torpedo nAChR positive and negative allosteric modulators (Nirthanan et al, 2008;Hamouda et al, 2011Hamouda et al, , 2014Jayakar Fig. 10.…”
mentioning
confidence: 46%
“…Centrifugation assays (Hamouda et al, 2011) H]PCP (1Carb, 6300 mM proadifen, 9000 6 80/1310 6 15 cpm; 1a-BgTx, 6300 mM tetracaine, 3300 6 90/1520 6 15 cpm); and for [ 3 H]tetracaine (1 a-BgTx, 6 300 mM tetracaine, 23,600 6 1800/4360 6 35 cpm). For direct [ using eqs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In accord, the side chains of the substituted residues in the PNU-resistant mutant extend into this cavity and increase the EC 50 for potentiation ∼30-fold (15). Anesthetics, alcohols, and neurosteroids are thought to bind to a similar location in GABA A and glycine receptors (21-23), photoactivatable hydrophobic probes label nearby residues in the Torpedo acetylcholine receptor (24)(25)(26), and X-ray structures of a prokaryotic homolog show anesthetics interacting with residues lining the cavity (27). This intrasubunit site in α7 is distinct from the site for the potentiator ivermectin, which spans transmembrane α-helices from adjacent subunits in the invertebrate Cys-loop receptor, GluCl (28).…”
Section: Discussionmentioning
confidence: 99%
“…Photoaffinity labeling studies have identified three classes of binding sites for allosteric modulators in the Torpedo nAChR TMD: 1) sites in the ion channel for "classical" cationic channel blockers, including chlorpromazine (Revah et al, 1990;Chiara et al, 2009) and tetracaine (Gallagher and Cohen, 1999), as well as uncharged, hydrophobic drugs, including the general anesthetics etomidate and propofol (Pratt et al, 2000;Ziebell et al, 2004;Nirthanan et al, 2008;Hamouda et al, 2011;Jayakar et al, 2013); 2) a site at the g2a subunit interface that binds positive (Nirthanan et al, 2008) and negative modulators (Hamouda et al, 2011;Jayakar et al, 2013); and 3) a site for negative modulators, including halothane and propofol, within the d subunit helix bundle (Chiara et al, 2003;Arevalo et al, 2005;Hamouda et al, 2008;Jayakar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%